Sources for Scientific Frustrations: Productivity and Citation Data - Zauder, Krešimir (Array, 2011)
The paper discusses usage of citation indices and similar databases as the source of data for determining scientific professional advancement. A short study on per-author basis, using Web of Science, Scopus, Google Scholar, Croatian scientific bibliography and online catalogue of the National and University Library in Zagreb, has been undertaken and shows disparate results for usage of these resources in mentioned context. Various problems surrounding such studies are discussed. Data complementation and especially firmer, more interconnected, national databases are recommended. Authors primary recommendation is thus to connect current national sources in a more wholesome system providing quality access to bibliometric data in this context. Fragments of the system are already present and usable: Crosbi (scientific bibliography), NSK (national catalogue), Hrčak (journal full text database)). This would impact both the self-consciousness of the individual scientist and the scientific politics bypassing the colonial and provincial mentality imposed by the monopoly of “international” commercial databases. Such integrated model of wholesome representation and distribution of scientific production on national level would serve as an answer to problems inherent to usage of citation databases such as WoS and Scopus.